A case of ventricular tachycardia and cardiac arrest associated with sertraline and mirtazapine combination - Atmaca, Murad; Mermi, Osman (Tehran University of Medical Sciences, 2014)
A 67-year-old male suffering from depressive symptomatology was admitted to the inpatient clinic at Firat University School of Medicine; and his psychiatric evaluation revealed major depressive episode according to DSM-IV. He developed chest discomfort, chest pain and shortness of breath of acute onset accompanying pulseless ventricular tachycardia (VT) leading to cardiac arrest following sertraline and mirtazapine combination treatment. He died after two days in the Intensive Care Unit. The present case suggests that psychiatrists should be aware of unexpected cardiac events, especially when they use combination treatments.
Keywords: Cardiac arrest; Mirtazapine; Sertraline